The Effect Of Neuroticism And Occupational Stress On Suicide Ideation With Emotional Focused Coping As A Mediator In Police Officers Who Use Fire Arms - Yudi Hardiyanto (CV. Syntax Corporation Indonesia, 2023)
This study aims to determine the effect of neuroticism and occupational stress on suicide ideation with emotional focused coping as a mediator for Polri members who use firearms. Suicidal ideation is a psychiatric emergency caused by high stress and inappropriate coping strategies. Prolonged fatigue and work stress can increase the risk of suicide in police officers. Individual differences in personality traits can be a risk factor for the emergence of suicidal ideation. Emotional focused coping tends to be carried out by individuals if they feel that the problem situation they are facing cannot be changed by managing emotional responses and maintaining affective balance through behavior. This study used 4 psychological scales, namely the big five factor personality scale, the work stress scale, the suicide attribution scale, and the emotional focused coping scale. The subjects to be studied were 375 active members of the National Police who routinely carry firearms in carrying out their duties. Data analysis used in this study was the Linear Regression Model Mediation analysis technique (Path Analysis) using the SPSS (Statistical Product and Service Solution) program for Windows Release version 20. Based on the findings, neuroticism has a direct effect of -0.465 and an indirect effect direct effect of -0.123 on suicidal ideation among members of the National Police who own weapons, this indicates that neuroticism has an indirect effect on suicidal ideation. For Polri members who own firearms, work stress has a positive and statistically significant effect on suicide intentions, as well as a direct effect of 0.406 and an indirect effect regression coefficient of -0.076.